Dampak Perencanaan Pajak Penghasilan Pasal 21 terhadap Jumlah Pajak Penghasilan Tahunan - Arniati Arniati; Muammar Muammar (JURNAL INTEGRASI, 2012)
Tax planning is an ways to minimize taxes payable. Good tax planning is to take advantage of the rules relating to the tax savings sought. Basically all types of taxes can be made tax planning. One is an employee or a tax known as the income tax article 21. Employee income tax treatment of most companies deducted from income by employees, some with given tax benefits and partly paid by the employer choosing those alternatives are part of tax planning. Employee income tax paid by the employer will add to the cost of the company so it needs a review to reducing costs. This study aimed to examine more about how to reduce the cost of corporate tax if the tax is paid by the company. The trick is to reduce the incomes of employees who are subject to tax to the income which is not the object that is given in the form of facilities or pleasure. The results showed there is a decrease in the overall amount of tax to be paid when the company gives pleasure to all employees who are above the income tax taxable year Rp500.000.000. This is due to the difference in the tax rate of 5% of the corporate income tax rate of 25% personal income tax rate of 30%.